IMPLEMENTASI DEEP LEARNING PADA SIMULASI AUTONOMOUS DRIVE MENGGUNAKAN AIRSIM - Violla Gunova (Universitas Pendidikan Indonesia (UPI), 2020)
Autonomous Driving is one of the technologies available in Artificial Intelligence. This technology aims to facilitate human work related to driving. The application of this technology can be done by using one of the main capabilities found in Artificial Intelligence, namely Machine Learning. By using several methods found in Machine Learning, Autonomous Driving Technology can be formed and developed. This paper will discuss how to make Autonomous Driving technology using available methods and show the results obtained from using these methods.